Frequency and Risk Factors for Associated Lymphomas in Patients With Lymphomatoid Papulosis. (14th December 2015) - Cordel, Nadège; Tressières, Benoît; D'Incan, Michel; Machet, Laurent; Grange, Florent; Estève, Éric; Dalac, Sophie; Ingen‐Housz‐Oro, Saskia; Bagot, Martine; Beylot‐Barry, Marie; Joly, Pascal; ,
Abstract : Background: Lymphomatoid papulosis (LyP) is classified as an indolent cutaneous lymphoma, but outcome dramatically worsens if LyP is associated with lymphoma. The frequency of this association remains unclear in the literature. Here, we assess the frequency and risk factors of association between LyP and another lymphoma in an 11‐year retrospective study conducted in 8 dermatology departments belonging to the French Study Group on Cutaneous Lymphoma (FSGCL). Patients and Methods: Patients with LyP were identified and data extracted from the FSGCL registry between 1991 and 2006. Patients were followed up to January 2014. Age, sex, number of skin lesions, histologic subtype, and genotype were recorded at baseline. Risk factors were determined using univariate and multivariate analysis. Cumulative probability of association was calculated using the Kaplan‐Meier method. Results: We observed 52 cases of lymphomas (cutaneous, n = 38; systemic, n = 14) in 44 of 106 patients (41%). Lymphoma diagnosis was concomitant with or prior to LyP diagnosis in 31 cases and occurred during the course of LyP in 21 cases (cutaneous, n = 14; systemic, n = 7; median delay: 5 years; interquartile range: 1.5–7 years). In multivariate analysis, main prognostic factors for association between LyP and another lymphoma were older age (odds ratio [OR]: 1.05 per year; 95% confidence interval [CI]: 1.01–1.08; p = .011) and presence of a T‐cell clone in LyP lesions (OR: 7.55; 95% CI: 2.18–26.18; p = .001). Conclusion: Older age and presence of a T‐cell clone in LyP lesions are risk factors for associated lymphomas in patients with LyP. These findings should help to identify patients who require close management in clinical practice. Implications for Practice: The management of lymphomatoid papulosis (LyP) is that of an indolent cutaneous lymphoma, based on its excellent prognosis. However, this good prognosis is altered if LyP is associated with lymphoma. Furthermore, risk factors for and frequency of this association remain unclear in the literature. The results presented here demonstrate a high rate of association between LyP and other lymphomas (41%) as well as a long median delay of occurrence (5 years), which emphasizes the need for prolonged follow‐up of patients with LyP. Moreover, two main risk factors (i.e., older age and presence of a T‐cell clone in LyP lesions) are highlighted, which should help clinical practitioners to identify patients who require close management. Abstract : The frequency and risk factors for association between lymphomatoid papulosis (LyP) and another lymphoma were assessed in an 11‐year retrospective study. Among 52 cases of lymphomas in 44 patients, lymphoma diagnosis occurred during the course of LyP in 21 cases (median delay: 5 years). Older age and presence of a T‐cell clone in LyP lesions were the main prognostic factors for association between LyP and another lymphoma.